Herbivory-induced Defense Responses in Brassicaceae: Implication on Secondary Metabolites Enrichment and Diversification - A Comprehensive Review - Suci Indah Putri; Shyla Aulia Delfi; Putra Santoso; Resti Rahayu; Muhammad Idris (Jurnal Biologi Tropis, 2026)
Plants of the Brassicaceae family display a highly complex and adaptive chemical defense system against biotic stresses, particularly herbivore attack. These defense mechanisms are physiologically based on the biosynthesis and activation of secondary metabolites, mainly glucosinolates, which are converted into toxic compounds such as isothiocyanates by the enzyme myrosinase upon tissue damage. This response is not only local, but also systemic, involving cross-interactions between roots and leaves, and is modulated by the hormones jasmonate (JA), salicylate (SA), and ethylene (ET). These complex interactions form a plant defense system that can be explicitly induced depending on the type and sequence of herbivore attack. In addition, molecular adaptation strategies, such as MYB gene expression, and engineering technologies, such as CRISPR/Cas9, have opened up opportunities to improve plant resistance. This study aims to analyze the physiological dynamics of Brassicaceae defense mechanisms, evaluate the role of hormonal and genetic regulation in enhancing plant resistance, and address the critical challenges posed by specialist herbivore adaptations and the socio-environmental implications of genetic engineering. By synthesizing these elements, this article presents a comprehensive review of the potential of these defense systems in advancing sustainable agriculture and promoting human health.